Non-audit services in Ukraine: the need for regulatory harmonization - I.О. Makarenko (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
Tightening the requirements for the audit profession and improving the quality of non-audit services led to best practice sharing of such services. The article analyzes the key trends in the provision of non-audit services in Ukraine in the context of implementing global experience. The comparative analysis of the requirements for separation of audit and non-audit services is conducted. The need for harmonization to ensure the independence of auditors in Ukraine is grounded. The author gives the particular attention to contemporary approaches to the regulation of such services in the EU and the US. So, the deep analysis of Directive 2014/56/EU «On statutory audits of annual accounts and consolidated accounts», Directive 2014/95/EU «Оn disclosure of non-financial and diversity information» and Sarbanes-Oxley Act is used by authors. In this regard, the gaps in regulatory control of audit and non-audit services in Ukraine are identified and the ways of their solution in the context of the reform of audit and convergence of accounting and auditing standards are underlined.